2019
DOI: 10.1177/0305735619883681
|View full text |Cite
|
Sign up to set email alerts
|

Subvocalization in singers: Laryngoscopy and surface EMG effects when imagining and listening to song and text

Abstract: Subvocalization has been described as a series of attenuated movements of the vocal tract during silent reading and imagination. This two-part study investigated covert laryngeal activations among singers during the perception and imagination of music and text. In the first part, 155 singers responded to an online survey investigating their self-perceived corporal activation when listening to live or recorded singing. Respondents reported frequent corporal activation in their larynx and other body parts in res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Alternatively, it may be that this result reflects the fact that vocal mimicry (and other types of mimicry) are not sufficient to induce emotion. It is worth noting that two recent studies also suggest that vocal simulation does not play as big a role in music perception as proposed by embodied cognition theories: Bruder and Wöllner (2021) found that subvocalization effects were present when participants imagined music but not when they listened to it; and Weiss et al (2020) found that engaging the vocal muscles in distracting tasks (such as chewing gum, or singing) did not have a detrimental effect on the participants’ recall for vocal melodies. Similarly, our results do not support the prediction that engaging in a distracting task would have a hampering effect on the participants’ affect.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Alternatively, it may be that this result reflects the fact that vocal mimicry (and other types of mimicry) are not sufficient to induce emotion. It is worth noting that two recent studies also suggest that vocal simulation does not play as big a role in music perception as proposed by embodied cognition theories: Bruder and Wöllner (2021) found that subvocalization effects were present when participants imagined music but not when they listened to it; and Weiss et al (2020) found that engaging the vocal muscles in distracting tasks (such as chewing gum, or singing) did not have a detrimental effect on the participants’ recall for vocal melodies. Similarly, our results do not support the prediction that engaging in a distracting task would have a hampering effect on the participants’ affect.…”
Section: Resultsmentioning
confidence: 94%
“…Several brain areas associated with music perception are also associated with vocalizing and motor planning (Brown & Martinez, 2007; Callan et al, 2006; Chen et al, 2008; Miller, 2016); and brain motor planning areas are activated during music listening (Gordon et al, 2018; Wallmark et al, 2018), especially in musicians (Alluri et al, 2017). Subvocalization (subtle movements of muscles related to vocal production) has been observed during musical mental imagery tasks (Pruitt et al, 2019;—but not during listening: Bruder & Wöllner, 2021). And TMS of pianists’ left-hand brain areas hampers their ability to play along with their right hand while listening to music that they previously learned to play with both hands (Novembre et al, 2014), or while synchronizing their right hand with a left-hand part recorded by a different pianist (Timmers et al, 2020).…”
mentioning
confidence: 99%
“…Also, occasional singers are more accurate at matching the absolute pitch heights of target tones from a vocal model than an instrumental one (Granot et al, 2013;Watts & Hall, 2008), especially when the model is one's own voice (Hutchins & Peretz, 2012;Moore et al, 2008). More broadly, evidence for the role of covert vocal-motor activity in auditory perception has been demonstrated in behavioral (e.g., Wood et al, 2020) as well as neurophysiological studies (e.g., Brown & Martinez, 2007;Bruder & Wöllner, 2021;D'Auselio et al, 2011;Pruitt et al, 2019). Evidence for vocal-motor mapping here was indirect and modest; in Experiment 1, explained variance for the vocal constraints model on the subset of female listeners (who should have greater registral overlap with the sung stimuli) improved from 75% to 77%, and the effect size of timbre in the upper condition of Experiment 2 improved for female listeners (from η 2 G = .078 to .084).…”
Section: Discussionmentioning
confidence: 99%
“…That these are largely innate responses helps explain the group synchrony discussed in Section 3—if one person responds in this way to a musical line, others are likely to respond similarly, the behavior being reinforced by positive feedback fostered by cultural transmission. Perceptual-cognitive … embodied linkages also engage an additional component, especially with singing-style musemes: a degree of pseudo-vocalisation on the part of the receiver (and sometimes the producer 28 ) in which the vocal tract silently traces the contour of the melodic line by tensing and relaxing the vocal cords in such a way as to “prime” the required pitches, but often without the expiration of air that would produce audible vocalisations (Bruder and Wöllner, 2021 ).…”
Section: Music Memes and Embodimentmentioning
confidence: 99%